ChemInform Abstract: Structural, FT‐IR, XRD and Raman Scattering of New Rare‐Earth‐Titanate Pyrochlore‐Type Oxides LnEuTi2O7 (Ln: Gd, Dy). Issue 33 (25th July 2013) - Garbout, A.; Taazayet‐Belgacem, I. Ben; Ferid, M.
Abstract Single‐phase samples of LnEuTi2O7 (Ln: Gd, Dy) are prepared by solid state reaction of stoichiometric mixtures of TiO2, Eu2O3, and Ln2O3 (1.